25 Years Later, Marxism Remains a Tool for Our Struggle. (28th August 2022) - Mathenge, Brian
Abstract : Brian Mathenge notes the actions of successive regimes in Kenya in overseeing the suppression of staunch Marxists and progressives who seemed a threat to the establishment - including political assassinations and arrests of those who happened to have different perspectives or ideological orientation - primarily because the ruling class was (and still is) frightened by efforts to educate and develop the consciousness of the masses. But as he reminds us, young cadres from the Social Justice Centre's are today adopting Marxism as a tool for struggle, and 25 years after the publication of Kenya: A Prison Notebook, a defiant generation with a fighting spirit is ready to advance the struggle for socialism as a generational mission.